Safety of median nerve electrical stimulation in disorders of consciousness: A systematic review and meta-analysis of randomized controlled trials - Chunling Gu; Hongcai Shang; Yifan Kong; Mengqi Peng; Huiru Jiang; Shijia Wang; Xiaohong Wei (PLoS ONE, 2025)
Background Median nerve electrical stimulation (MNS) is a noninvasive treatment technique that can improve the brain functional activity of patients with disorders of consciousness (DoC) and promote their awakening. However, there is no research on whether MNS increases the incidence and severity of DoC complications. In this study, we evaluated the safety of MNS for the treatment of DoC. Methods We searched relevant studies in PubMed, Cochrane, Web of Science (Medline), and Chinese databases, including CNKI, VIP, and WanFang Databases. For dichotomous outcomes, the pooled risk ratio (RR) with its 95% confidence interval (CI) was used as the effect estimate. We applied a fixed-effects or random-effects model to test the robustness of the forecast. A funnel plot was used to test for publication bias. Heterogeneity was evaluated using I². Subgroup analysis, sensitivity analysis were also performed. The quality of evidence was assessed using the GRADE approach. This study protocol has been registered in PROSPERO. Results The results of the meta-analysis showed that MNS may not increase the incidence of complications and adverse events such as seizures, increased sympathetic activity, arrhythmia, nausea and vomiting, lethargy, pulmonary infection, intracranial hemorrhage or hematoma, and gastrointestinal bleeding in DoC patients. However, the methodological quality of most studies was poor, and accurate conclusions could not be drawn. Conclusion MNS does not increase the incidence of DoC complications and adverse events, however, the quality of evidence for it’s safety is low and high-quality randomized controlled trials are needed to further confirm this conclusion.